Factors associated with mortality in patients affected by COVID-19. - da Silva Moreira, Cindhy Mífia; Lopes de Oliveira, Fabiana Maria Rodrigues; Batista Cabral, João Victor; Ferreira Brasil, Maria Hellena; Ferreira da Silva, Deysianne; Fernandes Barbosa, Keylla Talitha (Enfermería Global)
Objective: To investigate the clinical conditions and sociodemographic characteristics associated with mortality due to COVID-19 during the first year of the pandemic in an intensive care unit in a capital city in northeastern Brazil. Method: This was an exploratory, retrospective documentary study based on secondary data obtained from medical records of patients admitted to an intensive care unit of a public hospital in northeastern Brazil. Data collection occurred between July and September 2021. The data were analyzed via descriptive and inferential statistics. The chi-square test, Fisher's exact test, Student's t test, and binary logistic regression modeling were employed. The study was approved by the Research Ethics Committee. Results: A total of 274 patients, predominantly male, mixed-race, and aged over 65 years, were included. The variables male sex, age 65 years or older, marital status (married), and length of hospital stay were significantly associated with clinical outcomes. Logistic regression analysis revealed that male individuals, those aged 65 years or older, those requiring invasive mechanical ventilation, and patients in the prone position had higher odds of mortality as an outcome. Conclusions: Observing the factors associated with mortality outcomes in patients affected by novel coronavirus infection can aid healthcare professionals and public health managers in decision-making.